2015
DOI: 10.1111/jth.12860
|View full text |Cite
|
Sign up to set email alerts
|

Body height, mobility, and risk of first and recurrent venous thrombosis

Abstract: To cite this article: Flinterman LE, van Hylckama Vlieg A, Rosendaal FR, Cannegieter SC. Body height, mobility, and risk of first and recurrent venous thrombosis. J Thromb Haemost 2015; 13: 548-54.Summary. Background: Tall people have an increased risk of a first venous thrombosis. Sedentary lifestyle has been shown to act synergistically with body height, especially during long-haul flights. Objective: To estimate the relation between height and risk of a first and recurrent venous thrombosis and a possible a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 19 publications
1
38
0
2
Order By: Relevance
“…Of these patients, 225 did not consent to participate in a follow‐up study on recurrent venous thrombosis (MEGA follow‐up study). Therefore, 4731 patients were followed from their first venous thrombotic event until 2008–2010 when they completed a questionnaire on recurrent venous thrombosis (Flinterman et al , ). This study has been approved by the Medical Ethics Committee of the Leiden University Medical Centre, and all patients gave written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…Of these patients, 225 did not consent to participate in a follow‐up study on recurrent venous thrombosis (MEGA follow‐up study). Therefore, 4731 patients were followed from their first venous thrombotic event until 2008–2010 when they completed a questionnaire on recurrent venous thrombosis (Flinterman et al , ). This study has been approved by the Medical Ethics Committee of the Leiden University Medical Centre, and all patients gave written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…Development of thrombotic events in obese individuals is also associated with longer hospital admissions and mortality rates [6, 7]. More recently, a number of important research papers have linked the length of legs [8] and height [9] with recurrent venous thrombosis or pulmonary embolism [10]. To date, there are multiple prophylactic antithrombotic regiments; however, risk stratification strategies for prevention of DVT based on anthropometric data need to be improved [11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is a growing body of evidence that in the non-cancer, height is a robust predictor of thrombosis. [5] We aimed to evaluate whether body composition measurements including height, BSA and lean body mass are related to increased risk of thromboembolism in cancer patients.…”
Section: Dear Sirmentioning
confidence: 99%
“…[9]Similarly, the MEGA (multiple environmental and genetic assessment of risk factors for venous thrombosis-study) study evaluated 4644 patients and found that tall men and women have an increased risk of first and recurrent venous thrombosis, possibly higher in combination with a sedentary lifestyle. [5] The Physicians Health Study data, in a cohort not specific to patients with cancer, body height was a strong risk factor for development of VTE in males, but not in females. [10]Similarly, Flinterman et al evaluated 4464 patients from 1999 to 2004 for an average of 5.1 years for development of first and recurrent DVTs[5] The study found that men had a 2.9 fold (95% CI 1.9–4.4) increased risk for first thrombosis if their height was between 195 and 200 cm and a 3.8 fold (95% CI 1.5–9.8) higher risk for those >200 cm.…”
Section: Dear Sirmentioning
confidence: 99%
See 1 more Smart Citation